Minimally Invasive Surfactant Administration for the Treatment of Neonatal Respiratory Distress Syndrome: A Multicenter Randomized Study in China - Han, Tongyan; Liu, Huiqiang; Zhang, Hui; Guo, Ming; Zhang, Xuefeng; Duan, Yang; Sun, Fuqiang; Liu, Xinjian; Zhang, Xiang; Zhang, Mingtao; Liu, Fang; Bao, Lisha; et al. (Frontiers in Pediatrics, 2020)
Background/Aims: Current guidelines for management of respiratory distress syndrome (RDS) recommend continuous positive airway pressure (CPAP) as the primary mode of respiratory support to spontaneously breathing preterm infants. Less invasive surfactant administration (LISA) and minimally invasive surfactant therapy (MIST) have been reported to reduce the incidence of bronchopulmonary dysplasia (BPD). We aimed to explore the applicability of minimal invasive surfactant administration (MISA) in China. Methods: MISA was a multicenter, randomized, clinical study conducted at 8 level III neonatal intensive care units (NICU). Spontaneously breathing infants born at 25+0 to 31+6 weeks’ gestation and progressively developed respiratory distress during the first 6 hours of life, randomized to receive minimal invasive or endotracheal intubation surfactant administration, i.e. MISA or EISA. The primary outcome was survival without BPD at 36 weeks corrected gestational age. Results: Demographic and clinical characteristics of the 151 infants receiving MISA were well matched with the 147 infants in EISA group. The comparison showed no clear benefits of MISA group on the incidence of bronchopulmonary dysplasia (BPD), but infants of EISA group had higher rates of patent ductus arteriosus (PDA) (60.5% vs 41.1%, p=0.001). The duration of surfactant infusion and the total time of surfactant administration of MISA group were significant longer than EISA group. A slight increased heart rate was noted 1 hour post surfactant administration in EISA group. In subgroup analysis, the comparison of 51 smaller (less than 30 weeks) preterm infants, named as MISAs (n=31) and EISAs (n=20), showed a significant reduction of BPD (29.0% vs 70.0%, p=0.004) and PDA (29.0% vs 65.0%, p=0.011). In the subgroup analysis of blood gas, arterial oxygen saturations (SaO2) value at 1-hour and 12-hour and partial pressure of arterial oxygen (PaO2) at12-hour in EISAs group were higher compared with MISAs group. Conclusion: Minimal invasive surfactant administration was no clear benefits on the incidence of BPD, but it was associated with reduced incidence of patent ductus arteriosus. It is a promising new therapy for extremely low birth weight infants with respiratory distress syndrome, but requires training more experienced clinician.